Bond-slip mechanisms of hooked-end steel fibers in self-compacting concrete - Cunha, Vitor M. C. F. (2008)
The experimental results of hooked-end steel fibers pullout tests on a self-compacting concrete medium are presented and discussed in this work. The influence of fiber embedment length on the fiber pullout behavior is studied. The role of the end hook of the fiber on the overall pullout behavior is also investigated by carrying out tests with fibers without its end hook, in order to separate the contribution of the frictional bond component from those derived from the mechanisms provided by the end hook of the fiber. Finally, the experimental bond-slip relationships are modeled by an analytical model.